182 Predictors of Six-Month Inability to Return to Work in Previously Employed Subjects After Mild Traumatic Brain Injury: A TRACK-TBI Pilot Study. (1st April 2022) - Yue, John K.; Phelps, Ryan R. L.; Hemmerle, Debra P.; Upadhyayula, Pavan S.; Winkler, Ethan A.; Deng, Hansen; Chang, Diana; Vassar, Mary; Taylor, Sabrina; Schnyer, David; Lingsma, Hester F.; Puccio, Ava; et al.
Abstract : INTRODUCTION: Return to work (RTW) is an important milestone of mild traumatic brain injury (mTBI) recovery. METHODS: Adult subjects from the prospective multicenter TRACK-TBI Pilot study with mTBI (GCS 13-15) who were employed at baseline, with completed three-and six-month RTW status, and three-month Acute Concussion Evaluation (ACE), were extracted. Univariate and multivariable analyses were performed for six-month RTW, focusing on baseline employment, three-month RTW, and three-month ACE domains (physical, cognitive, sleep, and/or emotional postconcussional symptoms (PCS)). Odds ratios (OR) and 95% confidence intervals [CI] were reported. RESULTS: In 152 patients aged 40.7 ± 15.0 years, 72% were employed full-time at baseline. Three- and six-month RTW were 77.6% and 78.9%, respectively. At three months, 59.2%, 47.4%, 46.1% and 31.6% scored positive for ACE physical, cognitive, sleep, and emotional PCS domains, respectively. Three-month RTW predicted six-month RTW (OR = 19.80, 95% CI [7.61-51.52]). On univariate analysis, scoring positive in any three-month ACE domain predicted inability for six-month RTW (OR = 0.10-0.11). On multivariable analysis, emotional symptoms predicted inability to six-month RTW (OR = 0.19 [0.04-0.85]). Subjects who scored positive in all four ACE domains were more likely to be unable to RTW at six-months (4 domains: RTW = 58.3%, vs. 0-to-3 domains: RTW = 9.5%; multivariable OR = 0.09 [0.02-0.33]). CONCLUSION: Three-month post-injury is an important time point at which RTW status and PCS should be assessed, as both are prognostic markers for six-month RTW. Clinicians should be particularly vigilant of patients presenting with emotional symptoms and/or with symptoms across multiple PCS categories, as these patients are at further risk of inability to RTW and may benefit from targeted evaluation and support.